Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai pada Kantor Kecamatan TNS Kabupaten Maluku Tengah - Soselissa, Hendry Ch; Killay, Mariana (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2020)
Abstract This study aims to discuss and analyze the Work Motivation of Employee Performance in the District Office of Teon Nila Serua, Central Maluku Regency. The benefit of this research is that it provides information about the Effect of Work Motivation on Employee Performance at the District Office of Teon Nila Serua, Central Maluku Regency. The results this hypothetical test of work motivation is significant for employee performance. Therefore the results of this study state that work motivation has a good relationship with employees, increasing employee work motivation is expected to obtain higher performance as well. On this basis work motivation variable (X) can be included as one variable requested for employee performance (Y) in the Teon Nila Serua District Office of Central Maluku Regency. Keywords : Work Motivation, Employee Performance